Pengaruh Nilai Taksiran terhadap Keputusan Nasabah Melakukan Gadai Emas Di Pegadaian Syariah - Mulyani Rizki (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The estimated value of an item determines the amount of the loan to be obtained, customers can obtain loans ranging from minimum loans to maximum loans based on the value of the collateral. The high and low value of the estimate will determine the customer's decision to make a pledge. According to Rambat Lupiyoadi and Hamdani quoted by R. Rama Riyan Jazulia, a high estimated value for a product can encourage customers' decisions to use services at pawnshops so that customers will give a positive response if the value generated from a product or service can provide benefits. according to their needs. Appraisal of pawned goods is carried out by appraisers who already have special expertise and experience in assessing pawned goods. In conducting the assessment of gold, usually the standard carat content used in jewelry generally ranges from 18 to 22 carats.21. Judging from the above phenomenon, the Estimated Value can be taken into consideration for customer decision making to pawn gold at a sharia pawnshop. The purpose of this study is to find out how the influence of the estimated value on the customer's decision to pawn gold at the Syariah Pawnshop The number of samples in this study was 88 respondents, this study used a quantitative approach. The data collection technique in this study used a questionnaire, and the sampling technique used the incidental sampling method using the slovin formula. The data obtained were then processed using the SPSS 25 application. The results of this study indicate that the value of tcount (4.917) > ttable (1.988) and a significance value of 0.000 <0.05, which means that partially the estimated value variable has a positive and significant effect on the customer's decision variable in pawning gold at Pegadaian Syariah.